The importance of healthy lifestyle behaviors in the prevention of cardiovascular disease - Kaminsky, Leonard A.; German, Charles; Imboden, Mary; Ozemek, Cemal; Peterman, James E.; Brubaker, Peter H. (Progress in cardiovascular diseases, 2022)
Cardiovascular disease (CVD) is the leading cause of death globally. Advancements in the treatment of CVD have reduced mortality rates, yet the global burden of CVD remains high. Considering that CVD is still largely a preventable disease, prioritizing preventative measures through healthy lifestyle (HL) behaviors is necessary to lessen the burden of CVD. HL behaviors, such as regular exercise, healthy eating habits, adequate sleep, and smoking cessation, can influence a number of traditional CVD risk factors as well as a less commonly measured risk factor, cardiorespiratory fitness (CRF). It is important to note that cardiac rehabilitation programs, which traditionally have focused on secondary prevention, also emphasize the importance of making comprehensive HL behavior changes. This review discusses preventative measures to reduce the burden of CVD through an increased uptake and assessment of HL behaviors. An overview of the importance of CRF as a risk factor is discussed along with how to improve CRF and other risk factors through HL behavior interventions. The role of the clinician for promoting HL behaviors to prevent CVD is also reviewed.